The Influence of Social Influence and Online Customer Reviews on Consumers' Repurchase Interest with Trust as a Mediation Variable on the Tokopedia Marketplace (Study on Students of the Faculty of Business Economics, Harapan University of Medan) - Maulidina Yuliani; Endang Sulistya Rini; Fadli (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze social influence and online customer reviews on repurchase interest through consumer trust in the Tokopedia Marketplace. The type of research used in this study is associative research. The population in this study is students of the Faculty of Business Economics, Harapan University of Medan with a sample taken in this study of 105 respondents. The withdrawal of the sample size was carried out by non-probability sampling using the purposive sampling method. The data used are primary data and secondary data obtained through a list of statements and documentation studies. The data analysis technique uses structural equation modeling (SEM) with the Smart PLS analysis tool version 3.0. The results of the study directly show that social influence has a positive and insignificant effect on repurchase interest, online customer reviews have a positive and significant effect on repurchase interest, social influence has a negative and insignificant effect on trust, online customer reviews has a positive and significant effect on trust, and trust has a positive and significant effect on repurchase interest. Then the results of the test that were carried out indirectly showed that trust was not able to mediate the relationship between social influence and repurchase interest, but trust was able to mediate the relationship between online customer reviews and repurchase interest.